Ventilatory strategy during liver transplantation: implications for near-infrared spectroscopy-determined frontal lobe oxygenation - Sørensen, Henrik; Grocott, Hilary P.; Niemann, Mads; Rasmussen, Allan; Hillingsø, Jens G.; Frederiksen, Hans J.; Secher, Niels H. (Frontiers in Physiology, 2014)
Background: As measured by near infrared spectroscopy (NIRS), cerebral oxygenation (ScO2) may be reduced by hyperventilation in the anhepatic phase of liver transplantation surgery (LTx). Conversely, the brain may be subjected to hyperperfusion during reperfusion of the grafted liver. We investigated the relationship between ScO2 and end-tidal CO2 tension (EtCO2) during the various phases of LTx. Methods: In this retrospective study, 49 patients undergoing LTx were studied. Forehead ScO2, EtCO2, minute ventilation (VE), and hemodynamic variables were recorded from the beginning of surgery through to the anhepatic and reperfusion phases during LTx. Results: In the anhepatic phase, ScO2 was reduced by 4.3% (95% confidence interval: 2.5% to 6.0%; P<0.0001), EtCO2 by 0.3 kPa (0.2 to 0.4 kPa; P<0.0001), and VE by 0.4 L/min (0.1 to 0.7 L/min; P=0.0018). Conversely, during reperfusion of the donated liver, ScO2 increased by 5.5% (3.8% to 7.3%), EtCO2 by 0.7 kPa (0.5 to 0.8 kPa), and VE by 0.6 L/min (0.3 to 0.9 L/min; all P<0.0001). Changes in ScO2 were correlated to those in EtCO2 (Pearson r=0.74; P<0.0001). Conclusion: During LTx, changes in ScO2 are closely correlated to those of EtCO2. Thus, this retrospective analysis suggests that attention to maintain a targeted EtCO2 would result in a more stable ScO2 during the operation.